Black Phosphorus Quantum Dots: A Fluorescence Probe for Metal Ions Based on Black Phosphorus Quantum Dots (Adv. Mater. Interfaces 7/2020). Issue 7 (14th April 2020) - Xu, Zhenyu; Hu, Liang; Yuan, Jun; Zhang, Yiyue; Guo, Yujie; Jin, Zhengyuan; Long, Fangchao; Long, Yaojia; Liang, Huawei; Ruan, Shuangchen; Zeng, Yu‐Jia
Abstract : In article number 1902075, Yu‐Jia Zeng and co‐workers successfully prepared black phosphorus quantum dots with green fluorescence emission, which can directly detect trace Hg 2+ and Cu 2+ ions without the help of organic molecules in both aqueous and organic phases. The fluorescence quenching mechanism are further explained based on the calculation of the electronic structure and adsorption energy.